Strangers in a strange land: how diversity professionals navigate their marginal leadership identity - Felix, Bruno; Brandão, Mariana Clementino; Mahadevan, Jasmin; Schmitz, Anja; Vaz, Samir Lótfi; Irigaray, Hélio Arthur Reis (Frontiers in Psychology, 2024)
The purpose of the present study was to understand how executives responsible for Diversity and Inclusion construct their identities while occupying positions of "Marginal Leadership," and how they deal with threats to such identities. We conducted qualitative and inductive research with Brazilian executives in 66 organizations, focusing on their experiences as leaders. In our resulting model, we theorized that leaders in positions of Marginal Leadership demonstrate little role clarity, resources, and confidence for the exercise of their activities, suffering threats to their identities, which are not observed in executives occupying positions in more traditional functions such as Finance, Production, and Marketing. Furthermore, we identified that Brazilian executives responsible for Diversity and Inclusion build three types of Relational Leadership in interaction with individuals in historically disadvantaged positions, and alongside executives in traditional positions. First, "Business Partner," focusing on performance -boundary segmentation. Second, "Injustice Repairer," focusing on inclusion -boundary segmentation. Third, "Paradox Manager," focusing on performance and inclusion -boundary integration. Finally, we found that threats to their identities vary according to the type of Marginal Leadership constructed. While "Business Partners" and "Injustice Repairers" tend to be seen as false representatives or politically inept, the "Paradox Manager" tends to be labeled as a "Fence Sitter." This study advances the understanding of role identities in positions with ambiguous expectations, integrating Identity Theory and Boundary Theory